TECHNOLOGICAL ENHANCEMENT OF PROFESSIONAL TRAINING OF FUTURE TRANSLATORS: FOCUS ON LOCALIZATION - Iuliia Golovatska (Інформаційні технології і засоби навчання)
Future translators need to be prepared for present-day circumstances to provide a localized international translation product that users worldwide will engage with equal vigor. The article highlights the author’s view on the technologization of professional training of future translators based on localization in the conditions of digitalization of higher linguistic education. To achieve the goal, various methods were used: a literature review (conducting a thorough review of the literature that includes current research, scientific articles, and methodologies on the technological enhancement of education); pedagogical practice analysis (identifying efficient digital technologies that demonstrate high efficiency and prevent educational losses, as well as analyzing successful practices of preparing aspiring translators for professional activities in general and localization in particular); and identification of effective digital technologies to improve education. In addition, a thorough comparison of digital technologies was conducted to assess their effectiveness in preparing future translators for localization. The study concluded that professional training should equip future translators with the skills to effectively use digital technologies in modern technological conditions, revolutionizing the training of translators through the digitization of translation education, with a special emphasis on localization. This approach improves educational progress by combining recursive and discursive paradigms, ensuring authenticity, promoting localization learning, and creating a transparent and flexible atmosphere in universities. The integration of digital technologies solves several important problems in education and guarantees its effectiveness: minimizing the time delay between exposure to new concepts and assessment of outcomes; the creation of a virtual and real foreign language environment that makes it possible to provide an individual learning trajectory focused on the abilities of students; improving control of knowledge, skills, and abilities; increasing the effectiveness of learning through interactivity, multimedia, and individualization.